2017
DOI: 10.1089/jwh.2016.5840
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Physical Intimate Partner Violence with Mental Health Diagnoses in the Nationwide Emergency Department Sample

Abstract: Objectives: We examined associations of physical intimate partner violence (PIPV) with selected mental health disorders using a nationally representative sample of emergency department (ED) discharges corresponding to men and women (18-64 years) from the 2010 Nationwide Emergency Department Sample. Methods: PIPV was determined using International Classification of Disease, 9th Revision, Clinical Modification (ICD-9-CM) external cause of injury code E967.3 (battering by spouse or partner). ICD-9-CM clinical cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 111 publications
(90 reference statements)
2
51
1
4
Order By: Relevance
“…Los datos encontrados evidencian que existe una relación significativa entre haber experimentado violencia y presentar psicopatología psiquiátrica. Es importante destacar que las mujeres víctimas de VPI presentaron síntomas más severos que las que no la sufrieron (Beydoun et al 2017;Golding, 1999;Rosales, Bedón, Díaz, Brioso, & Pacheco, 2016).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Los datos encontrados evidencian que existe una relación significativa entre haber experimentado violencia y presentar psicopatología psiquiátrica. Es importante destacar que las mujeres víctimas de VPI presentaron síntomas más severos que las que no la sufrieron (Beydoun et al 2017;Golding, 1999;Rosales, Bedón, Díaz, Brioso, & Pacheco, 2016).…”
Section: Discussionunclassified
“…El grupo de mujeres víctimas presentó síntomas de depresión leve, moderada y severa, mientras que las del grupo de comparación, que reportaron no experimentar violencia, presentaron síntomas de depresión en el rango mínimo (Beydoun et al 2017;Golding, 1999;Stein, & Kennedy, 2001). Estos hallazgos coinciden con lo descrito por otros autores que indican que los problemas psicológicos presentados por la mujer víctima de violencia en la pareja pueden ir de moderados a graves (Pérez & Escobar, 2011).…”
Section: Discussionunclassified
“…More generally, the neuropathological contributions to mild traumatic brain injury have been well-established (Romeu-Mejia et al, 2019) and the increased risk of mental health problems confidently identified (Perry et al, 2016). Nevertheless, the mental health consequences of intimate partner violence is almost always conceptualised in terms of social and emotional causality, with no mention of brain injury (Beydoun et al, 2016;Stewart and Vigod, 2019). Importantly, this is not simply a matter for researchers and the development of better theoretical models.…”
Section: Current Diagnostic Technology Defines the Limits Of The Funcmentioning
confidence: 99%
“…For this reason, intimate partner violence against women in the family is a health problem that affects not only women, but also all the family members and hence the society and states in a multidimensional way. It requires multidisciplinary cooperation to prevent it (Korkut and Owen, 2008;Kruse et al, 2011;Beydoun et al, 2017).…”
Section: Health Dimension Of Violence Against Womenmentioning
confidence: 99%
“…In Turkey, the overall health status of women exposed to physical or sexual violence by their husbands is twice worse than that of women who have never had any violence (HÜNEE, 2015). For this reason, women who are exposed to the physical, sexual, psychological or economic violence of their partners are twice as often as women who are not violent, and the use of primary health care institutions and emergency services for physical and mental health problems are twice as often as women who are not violent Beydoun et al, 2017). Late or incomplete provision of the necessary health services to women suffering from peer violence causes the worsening of women's health, loss of limbs, death, reduction of treatment compliance and quality of life, increase hospitalization rate and hospitalization period (Costa et al, 2018).…”
Section: Health Dimension Of Violence Against Womenmentioning
confidence: 99%